Associations between Red Blood Cell Transfusions and Necrotizing Enterocolitis in Very Low Birth Weight Infants: Ten-Year Data of a Tertiary Neonatal Unit - Justinas Teišerskas; Rūta Bartašienė; Rasa Tamelienė (Medicina, 2019)
Background and Objective: Necrotizing enterocolitis (NEC) remains an important cause of mortality in preterm neonates. There are many risk factors for NEC; however, probably the most controversial one is red blood cell transfusions (RBCT). The data concerning the link between NEC and RBCT has been conflicting. Therefore, we aimed to analyze the association between NEC and RBCT in Neonatal Intensive Care Unit (NICU) at the Hospital of Lithuanian University of Health Sciences. Materials and Methods: We used the Very Low Birth Weight (VLBW) Infants database to match all infants with ≥2a Bell’s stage NEC admitted between 1 January 2005 and 31 December 2014 (n = 54) with a control group (n = 54) of similar gestational age and birth weight and without NEC. We analyzed the charts of these infants and performed statistical analysis on 20 clinical variables including RBCT. Results: The main clinical and demographic characteristics did not differ between the two groups. All variables associated with RBCT (receipt of any RBCT, the number of transfusions and the volume transfused in total) were significantly higher in the NEC group both before the onset of NEC and throughout the hospitalization. RBCT increased the odds of NEC even after adjustment for confounding factors. In addition, we found that congenital infection was more abundant in the NEC group and increased the odds of NEC 2.7 times (95% confidence interval CI (1.1, 6.3), p = 0.024). Conclusions: A higher number and the total volume of RBCT are associated with an increased risk of NEC in VLBW infants. The presence of congenital infection might identify the infants at risk.